The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.4103/2319-4170.117889
|View full text |Cite
|
Sign up to set email alerts
|

In vivo morphometry of menisci of the knee in South Indians: A preliminary study

Abstract: The present study provides new information on the meniscal thickness and width in South Indians that can be used in planning of orthopaedic and arthroscopic surgeries of the knee joint. However, the study needs to be analyzed with a large sample size for the better interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
3
6
1
Order By: Relevance
“…The present radiological study showed that the mean of thickness of different parts of the medial meniscus was 5.57 ±0.65mm for anterior horn, 6.25 ± 0.68mm for mid-body and 7.01 ±0.82mm for posterior horn which are quite similar to those of Dhananjaya et al, [23] who examined eighty menisci from forty knee joints of Indian population using MRI and reported it as 6.3 ± 1.1mm, 5.2 ± 1.3mm and 6.9 ± 1.1mm, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present radiological study showed that the mean of thickness of different parts of the medial meniscus was 5.57 ±0.65mm for anterior horn, 6.25 ± 0.68mm for mid-body and 7.01 ±0.82mm for posterior horn which are quite similar to those of Dhananjaya et al, [23] who examined eighty menisci from forty knee joints of Indian population using MRI and reported it as 6.3 ± 1.1mm, 5.2 ± 1.3mm and 6.9 ± 1.1mm, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the mean thickness of different parts of lateral meniscus was 5.23 ± 0.68mm for anterior horn, 6.49 ±0.52mm for midbody and 6.92±0.72mm for posterior horn which are close to those of Dhananjaya et al, [23] who reported it as 4.8 ±0.7mm, 6.4 ± 1.1mm and 7.0±0.9 mm, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…SonneryCottet et al [24] demonstrated an arthroscopic technique for ALL visualization; however, they only managed to visualize the most proximal portion of the ligament. According to the anatomical and resonance parameters In this image, it is possible to observe the spreading of ligament fibers immediately before the meniscal insertion Surg Radiol Anat described, the ALL insertion in the meniscus region should correspond to the location with narrower meniscal width, as it could serve as a guide in a possible attempt at arthroscopic location of this structure [7,10]. Even with these findings, Dodds et al [8] believe that the structure inserted in this meniscal region is not the ALL because in their study, they did not find it continuing toward the tibia.…”
Section: Discussionmentioning
confidence: 99%